A Strategy to Simplify the Preparation Process of Perovskite Solar Cells by Co‐deposition of a Hole‐Conductor and a Perovskite Layer. Issue 43 (13th September 2016) - Ye, Senyun; Rao, Haixia; Yan, Weibo; Li, Yunlong; Sun, Weihai; Peng, Haitao; Liu, Zhiwei; Bian, Zuqiang; Li, Yongfang; Huang, Chunhui
Abstract : The feasibility of co‐depositing a hole‐conductor and a perovskite layer is demonstrated to simplify the preparation process of perovskite solar cells. The CuSCN incorporated in the perovskite layer can participate in forming the perovskite/CuSCN bulk‐heterojunction and accelerate hole transport effectively, which eventually leads to a maximum power conversion efficiency of 18.1% with almost no J – V hysteresis.